The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.amepre.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Disparities in Trends in High BMI Among California Adolescents, 2003–2012

Abstract: Introduction Because California is home to one in eight U.S. children and accounts for the highest Medicaid and Children’s Health Insurance Program spending, childhood obesity trends in California have important implications for the entire nation. California’s racial/ethnic diversity and large school-based data set provide a unique opportunity to examine trends by race/ethnicity, including understudied Asian and American Indian youth, which has not been possible using national data sets. This study examined ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Childhood obesity also appears to pattern by the school the child attends. While white adolescents in the US tend to have lower levels of obesity compared to African-American and Hispanic adolescents (8, 9), our research with Texas public middle school students found similar levels of obesity among these three ethnic groups when attending the same high economically disadvantaged schools (10). Adjusting for the school a child attends has also been found to eliminate racial/ethnic disparities for a range of other health-related outcomes in research on fifth grade children from three large metropolitan areas in the US, including witnessing of violence, health status, and quality of life, as well as PA and obesity (11).…”
Section: Introductionmentioning
confidence: 44%
“…Childhood obesity also appears to pattern by the school the child attends. While white adolescents in the US tend to have lower levels of obesity compared to African-American and Hispanic adolescents (8, 9), our research with Texas public middle school students found similar levels of obesity among these three ethnic groups when attending the same high economically disadvantaged schools (10). Adjusting for the school a child attends has also been found to eliminate racial/ethnic disparities for a range of other health-related outcomes in research on fifth grade children from three large metropolitan areas in the US, including witnessing of violence, health status, and quality of life, as well as PA and obesity (11).…”
Section: Introductionmentioning
confidence: 44%
“…Zhuang ethnicity was found to be near-significantly associated with a lower risk of NODB in this study. Given that Guangxi is the largest Zhuang autonomous region in China, and different genetics among different race and ethnic groups contributing to obesity and type 2 diabetes have been documented [21,22,23], a different genetic background may explain some of the differences seen in this study from others in China/Asia and abroad. In Japan, non-obese type 2 diabetes patients have been demonstrated as having a stronger genetic predisposition to type 2 diabetes than obese type 2 diabetes [24].…”
Section: Discussionmentioning
confidence: 89%
“…Surveillance allows us to monitor population health and thereby set public health priorities, including identifying subgroups at greatest risk for various negative health outcomes. California’s mandatory use of the Fitnessgram in grades 5, 7 and 9 can provide valuable data on the obesity epidemic 2,46 as long as these data are made publicly available for use by researchers, program implementers and policy makers.…”
Section: Discussionmentioning
confidence: 99%
“…2 The National Academy of Medicine recommends school-based body mass index (BMI) screening and reporting, noting that while schools are not the ideal setting for such assessments, many children do not have BMI assessed regularly by health care providers. 3 Reporting a child’s BMI to parents is a minimal-dose intervention, but its broad reach makes it a potentially valuable public health tool for addressing obesity.…”
Section: Introductionmentioning
confidence: 99%